2021
DOI: 10.3390/brainsci11010103
|View full text |Cite|
|
Sign up to set email alerts
|

Might Fibroblasts from Patients with Alzheimer’s Disease Reflect the Brain Pathology? A Focus on the Increased Phosphorylation of Amyloid Precursor Protein Tyr682 Residue

Abstract: Alzheimer’s disease (AD) is a devastating neurodegenerative disorder with no cure and no effective diagnostic criteria. The greatest challenge in effectively treating AD is identifying biomarkers specific for each patient when neurodegenerative processes have not yet begun, an outcome that would allow the design of a personalised therapeutic approach for each patient and the monitoring of the therapeutic response during the treatment. We found that the excessive phosphorylation of the amyloid precursor protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…However, the real strength of the method is its high specificity in detecting explicitly and exclusively APP-Tyr682 residue phosphorylation. The application of this methods on mononuclear cells from blood of patients with AD can definitely proof whether and in which level the increase in APP Tyr phosphorylation previously demonstrated by immunoprecipitation [ 16 ] is correlated to the specific APP Tyr682 residue. Even though the chromatographic peaks are very close and appear to be not completely separated, MS/MS technology enables to distinguish MQQNGYENPTYK and MQQNGYpENPTYK unambiguously by their different fragmentation pattern as demonstrated by EPI-MRM experiments.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…However, the real strength of the method is its high specificity in detecting explicitly and exclusively APP-Tyr682 residue phosphorylation. The application of this methods on mononuclear cells from blood of patients with AD can definitely proof whether and in which level the increase in APP Tyr phosphorylation previously demonstrated by immunoprecipitation [ 16 ] is correlated to the specific APP Tyr682 residue. Even though the chromatographic peaks are very close and appear to be not completely separated, MS/MS technology enables to distinguish MQQNGYENPTYK and MQQNGYpENPTYK unambiguously by their different fragmentation pattern as demonstrated by EPI-MRM experiments.…”
Section: Discussionmentioning
confidence: 72%
“…Previous evidence supports the hypothesis that changes in the APP Tyr682 phosphorylation status influences APP trafficking and promotes the amyloidogenic APP processing to generate Aβ in neurons [ 5 , 7 , 11 , 12 , 13 , 14 , 15 , 17 , 31 ]. Notably, we recently suggested that changes related to APP Tyr682 phosphorylation in fibroblasts may reflect Aβ-related abnormalities in the brain [ 16 ], thus emphasizing the promising potential of using APP Tyr682 phosphorylation levels to develop new diagnostic strategies and to optimize therapeutic approaches with better outcomes in patients who are included in clinical trials [ 5 , 6 , 16 ]. Indeed, all these promising results need the development of a selective and quantitative procedure for the APP Tyr682 phosphorylation detection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Abnormalities in mitochondrial bioenergetics have also been observed in sAD fibroblasts [ 29 , 39 , 289 ]. Decreased ATP levels, oxidative stress, and defects in calcium handling have been widely documented [ 29 , 39 , 290 , 291 ] (Fig.…”
Section: Mitochondrial Dysfunction In Fibroblasts Obtained From Ad Pd...mentioning
confidence: 99%